The Use of Grammar Learning Strategies by Libyan EFL Learners at Sebha University - Safia Mujtaba Alsied; Noura Winis Ibrahim; Mustafa Mubarak Pathan (Lecturer Association of Linguistics, Language Teaching, and Literature Studies in Indonesi, 2018)
For most English language learners, grammar can be a very hard subject and some students tend to use different types of strategies to learn grammar. Using learning strategies is very beneficial as they facilitate the learning process and make it more controlled, enjoyable and effective for learners. This study explores the grammar learning strategies used by Libyan EFL undergraduate students at the English Department of Sebha University and the most frequents used strategies. The study also aims to find out if there is a significant difference between the students' use of learning strategies and gender. The population of the study were 121 Libyan EFL undergraduate students who are currently in their first and second years. Data was collected through questionnaire distributed to the participants in the class. The result of the study revealed that Libyan EFL learners used different types of grammar learning strategies which included memory strategies, metacognitive strategies, socio-affective strategies and cognitive strategies which were the least frequent used ones. It was found that the most frequent used strategies were memory strategies. The findings also showed that there is no significant difference between the use of grammar learning strategies and the participants' genders.